2019
DOI: 10.1016/j.tranon.2019.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Immunotherapies and Humanized Mouse Drug Testing Platforms

Abstract: Cancer immunotherapy is a type of treatment that restores and stimulates human immune system to inhibit cancer growth or eradicate cancer. It serves as one of the latest systemic therapies, which has been approved to treat different types of cancer in patients. Nevertheless, the clinical response rate is unsatisfactory and the response observed is mostly a partial response in patients. Despite the continuous improvement and identification of novel cancer immunotherapy, there is a pressing need to establish a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 121 publications
0
33
0
Order By: Relevance
“…Blinova et al used humanized NSG mice to test PDL-1 blocker durvalumab and demonstrated PDL-1 expression in PDX models with significant stagnation of tumor growth [73]. It is hoped that further development of humanized mouse PDX models will allow for the study of the interaction of the tumor and the human immune system, as early models suggest that both therapeutic outcomes and side effects can be recapitulated [82].…”
Section: Immunotherapy Testingmentioning
confidence: 99%
“…Blinova et al used humanized NSG mice to test PDL-1 blocker durvalumab and demonstrated PDL-1 expression in PDX models with significant stagnation of tumor growth [73]. It is hoped that further development of humanized mouse PDX models will allow for the study of the interaction of the tumor and the human immune system, as early models suggest that both therapeutic outcomes and side effects can be recapitulated [82].…”
Section: Immunotherapy Testingmentioning
confidence: 99%
“…Worth to mention is that due to their human like characteristics HTM are becoming increasingly important in the field of preclinical treatment studies. The value of mice with a human immune system to evaluate treatment success, failure and side effects involved has been recently highlighted by the US Food and Drug Administration [31,32]. Importantly, in TM (i.e., in the absence of human immune cells) the B100 treatment efficiency was not nearly as high as in HTM (i.e., in the presence of human immune cells).…”
Section: Discussionmentioning
confidence: 99%
“…The immunization with vaccines may reveal not only the effect of a specific vaccine, but it may also provide information regarding the patient immune response to mimic the anticancer/pathogen response. The current status of the humanized mouse system involving next generation humanized mice and its limitations is shown in Figure 1 (cellular immunity) and discussed below [95,96]. emerged as a distinctive side effect of ipilimumab and occasionally of nivolumab [92].…”
Section: Humanized Mouse Models For the Evaluation Of The Human Immunmentioning
confidence: 99%
“…The current status of the humanized mouse system involving next generation humanized mice and its limitations is shown in Figure 1 (cellular immunity) and discussed below. [95,96]…”
Section: Humanized Mouse Models For the Evaluation Of The Human Immunmentioning
confidence: 99%
See 1 more Smart Citation